Relationship between gingival bleeding and anaerobic periodontal infection assessed by BANA (N-Benzoyl-DL-Arginine-β-Napthylamide) assay - S Muthukumar; M Vijay Anand; Seenivasan Madhankumar (Wolters Kluwer Medknow Publications, 2014)
Background: Since periodontal diseases are primarily inflammatory in nature, the ability to detect inflammatory lesions in gingival tissue is essential for the diagnosis and monitoring of changes in gingival status. Gingival bleeding has been used as a reliable and objective clinical parameter not only for the evaluation of inflammatory conditions of periodontium, but also in the detection of its activity and progression. The gingival bleeding index (Loe) is based on the presence or absence of gingival bleeding, thereby provides a means of converting observed clinical data into statistical analysis. Periodontitis is widely regarded as a bacterial infection mainly mediated by subgingival plaque. N-benzoyl-DL-arginine β-naphthylamide (BANA) test is a simple chair side test used to detect, the specific enzymatic activity of microorganisms involved in periodontal disease. Objective: The objective of this study is to compare the clinical evaluation of the gingival index (GI) with the enzymatic BANA test. Materials and Methods: A total of 320 sites were selected from 20 patients with generalized chronic periodontitis, based on the presence are absence of gingival bleeding according to GI of Loe. Sub-gingival plaque samples were collected using a sterile curette and the BANA test was performed. Results: The distribution of GI and the intensity of the BANA test for the 320 sites analyzed during the initial examination of patients, with significance determined by the Chi-square test. The results were statistically significant at P ≤ 0.000. Conclusion: There was a direct relationship between positive BANA test results and GI scores, clearly demonstrating the validity of gingival bleeding as a significant diagnostic parameter. Clinical Significance: The validity of gingival bleeding as a clinical tool not only for the diagnosis of periodontal disease, but also in the detection of its activity and progression could be established by correlating the GI scores (which is based on the presence or absence of bleeding) with the primary etiologic factors (putative periodontal pathogens) assessed by BANA assay.